(untitled) (Research, Society and Development, 2021)
Objective: To describe the epidemiology of Sympathetic Nervous System Tumors in the State of Sergipe over 18 years. Methods: This is a cross-sectional, retrospective, quantitative study. Data were collected from the Population-Based Cancer Registry of the Pediatric Oncology Center located at the Sergipe State Reference Hospital. All patients aged between 0 and 19 years listed in the RCBP from 1996 to 2014 were included. Results: In Sergipe, between 1996 and 2014, 1705 cases of Childhood Cancer were registered, of which 45 (2.6%) were tumors of the Sympathetic Nervous System. There was a predominance of male patients (53.3%) and the most affected group were those under 5 years old (71.1%). An annual percentage growth rate of 0.08% over this period was observed. Conclusion: It was noticed that the incidence of TSNS is still low compared to other states in Brazil and other countries with more resources, which can highlight the importance of improving the diagnosis of tumors of the sympathetic nervous system in Sergipe.